Aluminium self-diffusion in high-purity α-Al2O3: Comparison of Ti-doped and undoped single crystals. (15th August 2020) - Fielitz, Peter; Ganschow, Steffen; Kelm, Klemens; Borchardt, Günter
Abstract: Reliable data on self-diffusion of aluminium in α-Al2 O3 are scarce and do not yet enable deriving quantitative conclusions about the impact of deliberate aliovalent doping. Therefore, the present study (1280 ≤  T / ° C  ≤ 1500, pO2  = 200 mbar) was based on carefully grown high-purity single crystals doped with Ti. The experimentally determined 26 Al tracer diffusivity increased with the Ti concentration and confirmed the incorporation of Ti on Al sites, T i A l, with aluminium vacancies, V A l ″ ′, formed for charge compensation. The observed relation between these two point defect concentrations as a function of the Ti concentration and the temperature can be quantitatively modelled by taking into account probable T i A l : V A l ″ ′ clusters. Using binding energy starting values from published computer simulations for the fit procedure cluster binding energies are obtained. The surprisingly high Al diffusivity in undoped samples can be tentatively rationalised by injection of Al interstitials at the liquid/solid interface because of the low oxygen potential during the crystal growth process. Graphical abstract: Image, graphical abstract